Estructura vegetal del bosque y su contribución a la captación de carbono en la reserva Pedro Franco Davila Jauneche–Ecuador. Año 2015. Propuesta de oferta de carbono - Bajaña Quintana, Shirley (2016)
This research aims to determine the structure of the forest vegetation and their contribution to carbon capture in the experimental station Pedro Franco Dávila (PFD) for two plots in this natural area and two plots were installed in the intervention area; each divided into eight quadrants or sub-plots of 400 m2; the variables used for data collection in the field study were: diameter at breast height (DBH) and total height of different species; likewise it was established statistical parameters and data as consider: Absolute and relative abundance, dominance, the average volume and carbon storage in the shaft. In the natural area they found 23 species and 24 species the intervention area; in both plots the highest incidence family Moraceae. Given the plant structure having the forest and carbon storage may indicate that in the natural area the species that showed higher carbon storage is Tutumbe (Enterolobium cyclocarpum) with 50066 kg ha-1, followed by fine Moral species (Chlorophora tinctoria) with 48937 kg ha-1; and in the affected plot the species that showed higher carbon storage was Fernan Sanchez (Triplaris cumingiana) with 29219 kg ha-1, followed by the species Palma Real (Scheelea butyracea) with 16874 kg ha-1. Also in this study data storage Organic Carbon (CO) was observed, the values of storage of CO were obtained through laboratory analysis of soil; for the relationship between the CO content in soil and the level of calcium (Ca) to edáfico level, statistically table Tukey was used with an average error of 5% for the standard error of the mean (SEM), with soil depth of 20 to 40 cm in natural and intervened condition. The relationship between the level of Ca and the CO content in the soil, depending on the increase in organic matter available in the forest indicates that the coefficient of determination: 20 cm depth is 82%; and 40 cm depth is 75%. No significant difference was found in carbon storage.